O vínculo silogístico entre religião e Estado nas Lições sobre a filosofia da religião de Hegel (Revista Eletrônica Estudos Hegelianos, 2021)
In this article, I draw upon the connection between politics and religion from Hegelian Logic’s elements. In The Science of Logic’s Introduction (1812-1816), Hegel conceives the logical method as the explanation of a content that affirms itself as “the exposition of God as he is in his eternal essence” (WdL-I, p. 44). This assertion is enhanced in The Encyclopedia of the Philosophical Sciences in Basic Outline (1830), in which Hegel claims that Logic must be sought in order to support an understanding the interest taken “in in religion, the State, the law and ethical life” (Enz § 19 Z3). The connection through Logic between religion and politics highlights the sense of “process” in which God, whereas he is activity, constitutes himself as he interacts with the other of himself (world and human beings). The divine moving is composed out of the logical "parts" Singular (S), Particular (P) and Universal (U), and actualizes the truth through the syllogism U-P-S, improving itself from other three iterations: S-P-U, P-S-U, and S-U-P. The Universal transcendental level attempts to solve the joint between Objective spirit (State) and Absolute spirit (Religion). This article also evaluates the usage of the syllogisms to indicate the intersection of temporal and spiritual elements, as well as political and logical dimensions under the concept of “community” in Philosophy of Right (1821), the aforementioned The Encyclopedia, and the Lectures on the Philosophy of Religion (1821-1831).